To rewrite \(\sqrt[3]{-24}\) as a product of an integer and another irrational cube root, we start by factoring \(-24\).
First, note that \(24\) can be factored as:
\[
24 = 8 \times 3
\]
And since \(-24\) can be expressed as:
\[
-24 = -1 \times 24 = -1 \times (8 \times 3)
\]
Next, we take the cube root:
\[
\sqrt[3]{-24} = \sqrt[3]{-1 \times (8 \times 3)} = \sqrt[3]{-1} \times \sqrt[3]{8} \times \sqrt[3]{3}
\]
Since \(\sqrt[3]{-1} = -1\) and \(\sqrt[3]{8} = 2\), we have:
\[
\sqrt[3]{-24} = -1 \times 2 \times \sqrt[3]{3} = -2 \sqrt[3]{3}
\]
Thus, the expression \(\sqrt[3]{-24}\) can be rewritten as:
\[
\sqrt[3]{-24} = -2 \sqrt[3]{3}
\]
This is in the form of an integer and another irrational cube root.